Adults Born Small for Gestational Age at Term Have Thinner Peripapillary Retinal Nerve Fiber Layers Than Controls - Fieß A; Brandt M; Mildenberger E; Urschitz MS; Wagner FM; Grabitz SD; Hoffmann EM; Pfeiffer N; Schuster AK (Eye and Brain, 2022)
Achim Fieß,1 Marilena Brandt,1 Eva Mildenberger,2 Michael Siegfried Urschitz,3 Felix Mathias Wagner,1 Stephanie Desiree Grabitz,1 Esther Maria Hoffmann,1 Norbert Pfeiffer,1 Alexander Konrad Schuster1 1Department of Ophthalmology, University Medical Center of the Johannes Gutenberg University Mainz, Mainz, Germany; 2Division of Neonatology, Department of Pediatrics, University Medical Center of the Johannes Gutenberg-University Mainz, Mainz, Germany; 3Division of Pediatric Epidemiology, Institute for Medical Biostatistics, Epidemiology and Informatics, University Medical Center of the Johannes Gutenberg University Mainz, Mainz, GermanyCorrespondence: Achim Fieß, Department of Ophthalmology, Medical Center of the Johannes Gutenberg University Mainz, Langenbeckstr. 1, Mainz, 55131, Germany, Tel +49-6131-17-5150, Fax +49-6131-17-8495, Email Achim.fiess@gmail.comPurpose: Prenatal growth restriction is associated with impaired neurodevelopment in childhood. This study investigated the effects of being born small for gestational age (SGA) on peripapillary retinal nerve fiber layer (pRNFL) thickness in adults born at term.Methods: A retrospective cohort study was conducted with a prospective ophthalmologic examination of participants born at full-term (gestational age ≥ 37 weeks) between 1969 and 2002. All participants were examined with spectral-domain optical coherence tomography and grouped according to their birth weight in correlation to gestational age as former moderate (birth weight (BW) percentile 3rd to < 10th) and severe SGA (< 3rd percentile), normal (10th-90th percentile, AGA), and moderately (> 90th to 97th percentile) and severely (> 97th percentile) large for gestational age (LGA) adults (18 to 52 years).Results: Overall, 547 eyes of 285 individuals (age 29.9± 9.4 years, 151 females) born at term were included. Multivariable regression analyses revealed a strong association between a lower global pRNFL thickness in the severe SGA (B=− 8.99 [95%-CI: − 12.68; − 5.30] μm; p< 0.001) and in the moderate SGA groups (B=− 6.40 [95%-CI: − 10.29; − 2.50] μm; p=0.001) compared to the reference AGA group.Conclusion: Our results indicate that restricted fetal growth affects neurologic tissue development of the optic nerve head, particularly in individuals born severely SGA at term. This indicates that fetal growth restriction may exert disturbances in the development of neurologic tissue, which persists in adulthood.Keywords: birth weight, small for gestational age, large for gestational age, peripapillary retinal nerve fiber layer, optic nerve head, epidemiology